Julian Assange in his own words - Assange, Julian 1971- (OR Books, 2021)
The WikiLeaks publisher and free speech campaigner Julian Assange has, since April 2019, been remanded at a maximum security prison in London facing extradition to the United States over WikiLeaks' groundbreaking 2010 publications. Now, in this crisp anthology, Assange's voice emerges - erudite, analytic and prophetic. Julian Assange In His Own Words provides a highly accessible survey of Assange's philosophy and politics, conveying his views on how governments, corporations, intelligence agencies and the media function. As well as addressing the significance of the vast trove of leaked documents published by WikiLeaks, Assange draws on a polymathic intelligence to range freely over quantum physics, Greek mythology, macroeconomics, modern literature, and empires old and new. Drawing on his insights as the world's most famous free speech activist Assange invites us to ask further questions about how power operates in a world increasingly dominated by a ubiquitous internet. Assange may be gagged, but in these pages his words run free, providing both an exhortation to fight for a better world and an inspiration when doing so
Keywords: Politik; Whistleblowing; Transparenz; WikiLeaks; Assange, Julian / Quotations; WikiLeaks (Organization); Leaks (Disclosure of information); Whistle blowing; Freedom of information; Official secrets; Government information; Transparency in government; Privacy, Right of; Electronic surveillance; Electronic surveillance / Social aspects; Internet / Political aspects; Internet / Social aspects; Internet / Censorship; Assange, Julian; Quotations